National survey of risk factors for non-communicable disease in Vietnam: prevalence estimates and an assessment of their validity - Tan Van Bui; Christopher Leigh Blizzard; Khue Ngoc Luong; Ngoc Le Van Truong; Bao Quoc Tran; Petr Otahal; Seana Gall; Mark R. Nelson; Thuy Bich Au; Son Thai Ha; Hai Ngoc Phung; Mai Hoang Tran; et al. (BMC, 2016)
Abstract Background To estimate the prevalence of non-communicable disease (NCD) risk factors at a provincial level in Vietnam, and to assess whether the summary estimates allow reliable inferences to be drawn regarding regional differences in risk factors and associations between them. Methods Participants (n = 14706, 53.5 % females) aged 25-64 years were selected by multi-stage stratified cluster sampling from eight provinces each representing one of the eight geographical regions of Vietnam. Measurements were made using the World Health Organization STEPS protocols. Data were analysed using complex survey methods. Results Differences by sex in mean years of schooling (males 8.26 ± 0.20, females 7.00 ± 0.18), proportions of current smokers (males 57.70 %, females 1.73 %), and binge-drinkers (males 25.11 %, females 0.63 %), and regional differences in diet, reflected the geographical and socio-cultural characteristics of the country. Provinces with a higher proportion of urban population had greater mean levels of BMI (r = 0.82), and lesser proportions of active people (r = −0.89). The associations between the summary estimates were generally plausible (e.g. physical activity and BMI, r = −0.80) but overstated, and with some anomalous findings due to characterisation of smoking and hypertension by STEPS protocols. Conclusions This report provides an extensive description of the sex-specific and regional distribution of NCD risk factors in Vietnam and an account of some health-related consequences of industrialisation in its early stages. The STEPS protocols can be utilized to provide aggregate data for valid between-population comparisons, but with important caveats identified.